Sustainable anti-MRSA Gracilaria changii extract through molecular biotechnology approach - Shamsudin, Mariana Nor; Mohd Yaakob, Haslinda Ayu; M., Habsah (Sarawak Biodiversity Centre, 2008)
Global bacterial infection management has a universal trend involving the fight against antibiotic resistant strains. The pressing microbial resistance problem incurred high infectious disease burden and cost constraints, requiring application of newer, more expensive agents. An approach for treatment against an antibiotic resistant pathogen, MRSA, involving a combination therapy is investigated. In the present study, synergy was determined by the checkerboard assay. The effect in combination of commercial antibiotic and seaweed extract were screened on MRSA strain. Following the disc diffusion test, the checkerboard assay, giving the FIC index of 0.93 indicate that the seaweed extract works in synergy with commercial antibiotics and it has the potential as a resistance modulator. In view of the fact that there was positive effect of the extract, further study were conducted molecularly on several genes to study the effect of the extract in combination with antibiotic toward the selected genes through RT-PCR analysis as compared to effect of the extract alone. The synergy effect on resistant genes of MRSA, namely mecA and mecI showed different nucleotide sequence changes as compared to untreated. The promising application of local G. changii as an antiMRSA agent is an added value to mega-diversity tropical flora.